Metallic cobalt to spinel Co3O4-electronic structure evolution by near-ambient pressure photoelectron spectroscopy - Reddy, Kasala Prabhakar; Jain, Ruchi; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
In the present study, valence band (VB) and core level photoelectron spectroscopy was carried out to investigate the electronic structural changes from polycrystalline Co to spinel Co3O4, via CoO at near ambient pressures (NAP; similar to 0.1). O-2 Co and H-2-CoOx gas solid oxidative and reductive interactions, respectively, have been explored with UV photons (He I) or low kinetic energy electrons (<= 16 eV) under NAP conditions. Typical VB features of Co metal, CoOx Co3O4, and a mixed phase between any two adjacent features were observed and well corroborated with core level changes. Very significant and characteristic changes were observed with Co 3d features in the VB for each stage from Co oxidation to Co3O4 as well as Co3O4 reduction to CoOx Co(3O)4 and CoO can be reversibly obtained by alternating the conditions between 0.1 mbar of H-2 at 650 K and 0.1 mbar of O 2 at 400 K, respectively. A meaningful correlation is observed between the changes in work function with cation oxidation state; small changes in the stoichiometry can strongly influence the shift in Fermi level and changes in work function under NAP conditions. Reversible work function changes are observed at a constant BE (similar to 5 ev) between oxidation and reduction conditions. While the O 2 p derived feature for CoOx was observed at throughout the redox conditions, the Co 3d band and molecular oxygen or hydrogen vibration feature shifts significantly underscoring the physicochemical changes, such as charge transfer energy and hence changes in satellite intensity. The peak close to E-F originated from the 3d(6)L final state of the octahedral Co3+ 3d band of Co3O4.

Mapping valence band and interface electronic structure changes during the oxidation of Mo to MoO3 via MoO2 and MoO3 reduction to MoO2: A NAPPES study - Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Tuning the surface energetics, especially work function (phi) of the materials, is of a great deal of interest for a wide range of surface- and interface-based devices and applications. How the phi of a solid surface changes under the reaction conditions is of paramount interest to the chemists, particularly in the areas of surface dependent phenomena such as, catalysis and electrochemistry. In the present study, by using the valence band and core-level photoelectron spectroscopy, surface-electronic changes from Mo to MoO3 via MoO2 was studied under relevant near-ambient pressure (NAP) and high temperature conditions. A very significant change in phi from Mo to MoO3 was observed and it is well corroborated with the changes in gas-phase vibrational features of O-2 in both near-ambient pressure ultraviolet photoelectron spectra (NAPUPS) as well in NAP X-ray photoelectron spectroscopy. Reversible changes in the electronic structure is observed when MoO3 was reduced in H-2 to MoO2. On the basis of the extent of oxidation/reduction of MoOx NAPUPS has shown, one or two additional peaks in the band gap at 0.6 and 1.6 eV below the Fermi level. Mo5+ features are identified in the VB and in the Mo 3d core levels with distinct features. Mo5+ features are also stable and essential to bridge MoO2 and MoO3 layers, and their co-existence. In addition, characteristic changes in Mo 4d and O 2p features observed from Mo to MoO3 and well corelated to the band gap of MoO3. Oxidation and reduction propagate from the surface to bulk; indeed, this has significant implications in surface-dependent phenomena. The present study demonstrates (a) the uniqueness of NAPUPS in identifying the subtle to large changes in the electronic structure on solid surfaces under common oxidation and reduction (in general, under reaction) conditions, and (b) relevance of NAPUPS to all surface dependent phenomena, such as catalysis and electrochemistry.